Location and severity of root resorption related to impacted maxillary canines: a cone beam computed tomography (CBCT) evaluation - Doğramacı Esma J.; Sherriff Martyn; Rossi-Fedele Giampiero; McDonald Fraser (Sciendo, 2015)
The present investigation was designed to determine the location and severity of root resorption associated with impacted maxillary canine teeth using cone beam computed tomography (CBCT). A secondary aim was to identify possible influencing factors.